Non-destructive Residual Stress Analysis Around The Weld-Joint of Fuel Cladding Materials of ZrNbMoGe Alloys - Parikin Parikin; Bandriyana Bandriyana; I. Wahyono; A.H. Ismoyo (PPIKSN-BATAN, 2013)
The residual stress measurements around weld-joint of ZrNbMoGe alloy have been carried out by using X-ray diffraction technique in PTBIN-BATAN. The research was performed to investigate the structure of a cladding material with high temperature corrosion resistance and good weldability. The equivalent composition of the specimens (in %wt.) was 97.5%Zr1%Nb1%Mo½%Ge. Welding was carried out by using TIG (tungsten inert gas) technique that completed butt-joint with a current 20 amperes. Three region tests were taken in specimen while diffraction scanning, While diffraction scanning, tests were performed on three regions, i.e., the weldcore, the heat-affected zone (HAZ) and the base metal. The reference region was determined at the base metal to be compared with other regions of the specimen, in obtaining refinement structure parameters. Base metal, HAZ and weldcore were diffracted by X-ray, and lattice strain changes were calculated by using Rietveld analysis program. The results show that while the quantity of minor phases tend to increase in the direction from the base metal to the HAZ and to the weldcore, the quantity of the ZrGe phase in the HAZ is less than the quantity of the ZrMo2 phase due to tGe element evaporation. The residual stress behavior in the material shows that minor phases, i.e., Zr3Ge and ZrMo2, are more dominant than the Zr matrix. The Zr3Ge and ZrMo2 experienced sharp straining, while the Zr phase was weak-lined from HAZ to weldcore. The hydrostatic residual stress (σ) in around weld-joint of ZrNbMoGe alloy is compressive stress which has minimum value at about -2.73 GPa in weldcore region. Received: 16 January 2013; Revised: 25 April 2013; Accepted: 10 June 2013